Does Removal of the Symphyseal Cartilage in Symphyseal Dislocations Have Any Effect on Final Alignment and Implant Failure?. Issue 10 (October 2015) - Lybrand, Kyle; Kurylo, John; Gross, Jordan; Templeman, David; Tornetta, Paul
Abstract : Objectives: To compare final symphyseal alignment, incidence of implant failure, and revision surgery with and without symphyseal cartilage excision in patients with symphyseal dislocations treated operatively. Design: Retrospective review. Setting: Two academic level 1 trauma centers. Patients/Participants: We reviewed the records of 96 patients (89 men, 7 women) who had anterior posterior compression (APC) type 2 and 3 injuries requiring anterior plating. The average age was 46 years, and the average Injury Severity Score was 15.6. Intervention: Fifty patients were treated with symphyseal cartilage removal, whereas a second cohort of 46 patients was treated without removal of the symphyseal cartilage at the time of symphyseal open reduction and internal fixation during the same time period in a different center. Operative indications were the same for both centers, with iliosacral screws used only for type 3 injuries. Both centers used 6-hole plates through a rectus sparing approach. Main Outcome Measurements: Symphyseal separation was measured radiographically on preoperative and postoperative anteroposterior (AP) and outlet projections. The incidence of implant failure was recorded from the final postoperative radiograph available. Revision surgery was documented. Results: The symphyseal space after cartilage excision was less than if retained, which was maintained through union. The incidence of implant failure was statistically lower when symphyseal cartilage was excised. There were 2 revisions of symphyseal fixation in the symphyseal retention group for implant failure versus none when excised. Conclusions: Symphyseal cartilage excision led to closer apposition of the symphyseal bodies, which correlated with substantially lower rates of implant failure, and revision surgery. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.